2007
DOI: 10.4049/jimmunol.178.5.2835
|View full text |Cite
|
Sign up to set email alerts
|

IL-2/Neuroantigen Fusion Proteins as Antigen-Specific Tolerogens in Experimental Autoimmune Encephalomyelitis (EAE): Correlation of T Cell-Mediated Antigen Presentation and Tolerance Induction

Abstract: The purpose of this study was to assess whether the Ag-targeting activity of cytokine/neuroantigen (NAg) fusion proteins may be associated with mechanisms of tolerance induction. To assess this question, we expressed fusion proteins comprised of a N-terminal cytokine domain and a C-terminal NAg domain. The cytokine domain comprised either rat IL-2 or IL-4, and the NAg domain comprised the dominant encephalitogenic determinant of the guinea pig myelin basic protein. Subcutaneous administration of IL2NAg (IL-2/N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(35 citation statements)
references
References 51 publications
1
34
0
Order By: Relevance
“…2D) or the synthetic gp69 -88 peptide (not shown). These data provide evidence that the cytokine domain may facilitate presentation of the NAg by professional APC, as was described for the IL4-NAg, IL2-NAg, and NAg-IL16 fusion proteins (25)(26)(27). Although the antigenic potency of IFN␤-NAg appeared greater than GPMBP as measured by the concentration eliciting a half-maximal response, the peak proliferative response stimulated by IFN␤-NAg was a Rats were pretreated with saline (first row), with 1 nmol of NAg (synthetic peptide gp69 -88) in saline (second row), or with 1 nmol of IFN␤-NAg in saline (third row) on days Ϫ21, Ϫ14, and Ϫ7 and were challenged with 50 g of DHFR-NAg in CFA on day 0.…”
Section: Biological Activity Of the Nag Domainmentioning
confidence: 69%
See 4 more Smart Citations
“…2D) or the synthetic gp69 -88 peptide (not shown). These data provide evidence that the cytokine domain may facilitate presentation of the NAg by professional APC, as was described for the IL4-NAg, IL2-NAg, and NAg-IL16 fusion proteins (25)(26)(27). Although the antigenic potency of IFN␤-NAg appeared greater than GPMBP as measured by the concentration eliciting a half-maximal response, the peak proliferative response stimulated by IFN␤-NAg was a Rats were pretreated with saline (first row), with 1 nmol of NAg (synthetic peptide gp69 -88) in saline (second row), or with 1 nmol of IFN␤-NAg in saline (third row) on days Ϫ21, Ϫ14, and Ϫ7 and were challenged with 50 g of DHFR-NAg in CFA on day 0.…”
Section: Biological Activity Of the Nag Domainmentioning
confidence: 69%
“…Previous studies of IL2-NAg and NAg-IL16 fusion proteins showed that covalent linkage of the cytokine and NAg domains was necessary for inhibition of EAE (25,26). That is, administration of a fused cytokine-NAg protein was tolerogenic, whereas administration of cytokine and NAg as separate molecules to the same inoculation site was without activity.…”
Section: Ifn␤-nag Fusion Proteins Prevented Eaementioning
confidence: 95%
See 3 more Smart Citations